Primary Diffuse Leptomeningeal Gliomatosis Mimicking Tuberculous Meningitis. (December 2014) - Kosker, Muhammet; Sener, Dicle; Kilic, Omer; Hasiloglu, Zehra Isik; Islak, Civan; Kafadar, Ali; Batur, Sebnem; Oz, Buge; Cokugras, Haluk; Akcakaya, Necla; Camcioglu, Yildiz
Primary diffuse leptomeningeal gliomatosis is a disease with an aggressive course that can result in death. To date, 82 cases have been reported. Here, the case of a 3-year-old male patient presenting with strabismus, headache, and restlessness is reported. Physical examination revealed paralysis of the left abducens nerve, neck stiffness, and bilateral papilledema. Tuberculous meningitis was tentatively diagnosed, and antituberculosis treatment was initiated when cranial imaging revealed contrast enhancement around the basal cistern. Craniocervical magnetic resonance imaging (MRI) was performed when there was no response to treatment, and it revealed diffuse leptomeningeal contrast enhancement around the basilar cistern, in the supratentorial and infratentorial compartments, and in the spinal region. Primary diffuse leptomeningeal gliomatosis was diagnosed by a meningeal biopsy.